Economic growth and unemployment alleviation in the development of MSMEs in Karawang Regency - Aliman, Aliman; Putra, Billy Perdana; Saputri, Sereniki Dwi Jayadi; Aprilia, Ghina Intan; Kurniati, Alia (International Journal of Applied Finance and Business Studies, 2024)
The Office of Cooperatives, Small and Medium Enterprises is a Regional Apparatus the Organization of Karawang Regency that has a role in efforts to improve the community's economy through the empowerment of cooperatives and small and medium enterprises. The main force behind economic development at the regional and national levels MSMEs are expected to be a pillar in regional economic development, so as to reduce unemployment. This research uses quantitative methods.  A sample of 100 MSMEs from the current 15,410 MSMEs (as reported by BPS Karawang 2022) was taken from various MSMEs in the Karawang Regency area. The data processing results passed the heterogeneous, multidisciplinary, auto correlation, and normality tests. The variables X1 and X2 represent economic growth and unemployment reduction, respectively. So that the two independent factors of economic growth and unemployment alleviation have a major impact on the dependent variable of MSME development, the test results according to hypothesis testing, in an effort to reduce unemployment in Karawang Regency, that the growth of MSMEs in the region can support economic expansion and have a positive impact on employment and regional economic independence.